Pernikahan Anak dan Konstruksi Sosial Budaya Generasi Z di Lombok Utara - Farida Hilmi; Lalu Wiresapta Karyadi; Sally Salsabila (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2025)
Child marriage remains a persistent socio-cultural problem in Indonesia, particularly in North Lombok. Economic limitations or education factors do not merely drive this Phenomenon. Still, it is deeply rooted in the local socio-cultural structures that regulate community behavior, particularly among Generation Z. This study aims to analyse the socio-cultural construction of child marriage among Generation Z in North Lombok through the theoretical perspective of social construction proposed by Peter L Berger and Thomas Luckmann. This Research employs a qualitative phenomenological approach to unpack practices, community structures, and symbolic power embedded in local tradition. The findings demonstrate that child marriage remains socially reproduced due to the internalisation of customary traditions such as merarik, religious legitimation, social stigma related to age norms, and the persistence of patriarchal gender relations embedded within local cultural institutions. Although the internet and social media provide alternative channels of information, these platforms have not significantly shifted long-standing communal values that shape individual decisions. Consequently, the construction of marital knowledge among Generation Z emerges through the dialectical processes of externalisation, objectification, and internalisation within familial settings, community life, and digital environments. The study concludes that the prevalence of child marriage among Generation Z in North Lombok is not solely a result of individual preferences, but rather are relations of socio-cultural forces that shape perceptions, meanings, and subsequent actions related to marriage.